Uncertainty of the smeared crack model applied to RC beams. (15th June 2020) - Rimkus, Arvydas; Cervenka, Vladimir; Gribniak, Viktor; Cervenka, Jan
Graphical abstract: Highlights: Smeared crack model based on fracture mechanics is verified by experiments. Comparable size of FE mesh and aggregates ensures adequate prediction of crack width. It is not relevant to include a bond stress-slip law in the numerical model. Abstract: A finite element model simulates concrete cracking using a smeared crack approach. The uncertainty of the crack width model is verified by the experimental data from tests of reinforced concrete beams. The parametric analysis of the numerical model includes the effects of the bond, fracture energy, and finite element mesh size. The model uncertainty analysis confirmed that the smeared crack model based on fracture mechanics could adequately predict the maximum crack width.